Faktor-Faktor yang Mempengaruhi Terjadinya Ketuban Pecah Dini pada Ibu Bersalin di Puskesmas Kedung 1 - Neneng Anisa; Ana Zumrotun Nisak; Nor Asiyah (Journal of Midwifery and Health Science of Sultan Agung, 2026)
Background: Premature rupture of membranes (PROM) is when the membranes rupture before labor and after waiting for one hour there are no signs of labor. Full-term or pre-term pregnancy can cause premature rupture of membranes, which increases the risk to the mother and fetus. In this study, factors that influence the possibility of premature rupture of membranes in pregnant women are discussed. such as parity, occupation, Smoking activity, Objective: To decide the components that impact the event of untimely crack of films in moms giving birth at the Kedung 1 Wellbeing Center Method: This study is a type of correlational research, namely examining the relationship between variables. With a sample size of 60 respondents, using a checklist filled in using Secondary data in this study were obtained by taking data on mothers giving birth with or without PROM accompanied by occupation, parity and family members who smoke. Analysis using the rho sperm test. Results: The results of the study showed that occupation obtained p rate 0.604, for parity obtained p rate 0.000 and for smoking activity p rate 0.000. Of the three results above, figure the impact the event of untimely crack of films in ladies giving birth at the Kedung 1 Community Helth Center include parity and smoking habits